Synthesis, Characterization, Antimicrobial and Theoretical Studies of V(IV),Fe(III),Co(II),Ni(II), Cu(II), and Zn(II)Complexes with Bidentate (NN) Donar Azo Dye Ligand (Baghdad Science Journal, 2025)
The new 4-[(7-chloro-2,1,3-benzoxadiazole)azo]-4,5-diphenyl imidazole (L) have been synthesized and characterized by micro elemental and thermal analyses as well as 1H.NMR, FT-IR, and UV-Vis spectroscopic techniques. (L) acts as a ligand coordinating with some metal ionsV(IV), Fe(III), Co(II), Ni(II), Cu(II), and Zn(II). Structures of the new compounds were characterized by elemental and thermal analyses as well as FT-IR and UV-Vis Spectra. The magnetic properties and electrical conductivities of metal complexes were also determined. Study of the nature of the complexes formed in ethanol following the mole ratio method.. The work also include a theoretical treatment of the formed complexes in the gas phase, this was done using the (hyperchem-8) program for the molecular mechanics and semi-empirical calculations. The heat of formation (?Hf?), binding energy (?Eb)and total energy (?ET) for ligand and their metal complexes were calculated by (PM3) method at 298 K.The electrostatic potential of the ligand (L) was calculated to investigate the reactive sites of the molecules. PM3 were used to evaluate the vibrational and electronic spectra for the ligand (L) and their metal complexes then comparing with the experimental values. The antibacterial activity for the (L)and its metal complexes were studied against two types of pathogenic bacteria Pseudonomous aerugionosa as gram negative and Bacillus subtilis as gram positive. Furthermore, the antifungal activity against two fungi Candida albicans, and Aspergillus flavus was studied for (L) and its metal complexes.